Strategy of Quality Improvement of Pond Shrimp Post Harvest Management (Penaeus monodon Fabricius) in Mahakam Delta (Case Study) - Andi Noor Asikin; S. Hutabarat; Y. S. Darmanto; S. B. Prayitno (International Journal of Science and Engineering, 2012)
Mahakam Delta area, which is situated in Kutai Kartanegara Regency, has become a pond center that gives a significant contribution to shrimp export of East Kalimantan Province. Pond-produced shrimps, however, do not always accord to the intention of cold storage companies at expected price. The companies even sometimes reject the request due to poor quality of the product. The decreasing shrimp quality may be due to maintenance process by the pond farmers as well as the improper collectors. In the other hand, importing countries have decided more and more restricted requirements for the imported fishing products. This study was held in Muara Jawa, Anggana, and Muara Badak Districts using techniques of data collection of in-depth interview with twelve respondents. In order to improve shrimp quality, farmers or the producers have to formulate a strategy towards the improvement of the post harvest shrimps from the pond using an Analytical Hierarchy Process (AHP). Results of the AHP consist of as follows: (1) application of pond shrimp post harvest technology and improvement of facilities and accommodation that support the quality improvement of the pond shrimps, (2) human resource quality improvement of pond farmers, collectors, and field instructors, (3) development of pond culture by applying best practices principle and local policies in order to improve the quality of the pond shrimps, and (4) improvement of interagency coordination, monitoring, and evaluation to enhance the pond shrimp quality